Critiquing cooperation - Kistin, E; Elizabeth J. Kistin (2011)
﻿ The purpose of this study is to develop a deeper understanding of the formation and performance of the international water management institutions operating in the Orange-Senqu basin shared between Lesotho, South Africa, Botswana, and Namibia. The research examines the influence of interstate interaction on adaptive capacity and the allocation of water and related benefits within the Orange-Senqu basin and provides explanations for how and why particular cooperative arrangements emerged and produce differential effects. By applying a structure-agent approach to regime analysis, this study draws attention to four key factors underpinning the formation and performance of the Orange-Senqu water governance regime: power asymmetry, problem structure (i.e., the combination of interest asymmetry and uncertainty), expert networks, and political context. The study demonstrates that each of these four factors provides important and complementary insight into the process of interaction of and the positive and negative effects produced by international water management institutions in the basin and opportunities for generating change. Among these factors, the study argues, power asymmetry and problem structure are critical for understanding transboundary water governance dynamics and identifying strategies for challenging the status quo.